UTILIZATION OF NATURAL ZEOLITE AS AN ADSORBENT IN ETHANOL PURIFICATION - Haryadi, H; Sariadi, S; Fona, Zahra (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Research about application of natural zeolite (ZA) as adsorbent to absorb water in ethanol has been started. The purpose is, to evaluate the ability of ZA that have been activated in order to absorb water in ethanol. The activator that used is H2SO4 1N and HCl 1N solution. ZA crushed and sieved using a sieve 60, 80, and 100 meshes. A total of 35 grams of sifted ZA mixed with the activator and stirred for 30 minutes and then precipitated for 24 hours. Residue washed until neutral and heated using a furnace at a temperature of 400oC for 2 hours. ZA which has activated used to adsorb the water content in ethanol having a concentration of 60 %, 65 %, 70 %, and 80 %. The results showed that the activated zeolite by using H2SO4 1N solution to absorb water content in the ethanol have the efficiency until 19.7 %. However, the adsorption of water content in ethanol which has more than 60 % concentration, ethanol tends to adsorbed by ZA so that the water content in ethanol to be slightly higher compared with ethanol before adsorption.Keywords: Adsorben, zeolit, water content, activated, adsorbtion.